Hydrographic variability in the Gulf of Papagayo, Costa Rica during 2017-2019 - Cambronero-Solano, Sergio (2021)
Introduction: The Gulf of Papagayo (GP) is a site of socioeconomic importance located in the North Pacific of Costa Rica. The ecosystem services of this site represent a benefit in local communities, and its dynamics are influenced by a coastal upwelling system that affects fishing and commercial activity. Objective: The objective of this study was to characterize the spatio-temporal variability of the main hydrographic parameters through measurements in situ during the period 2017-2019. Methods: Eight measurement campaigns were carried out, where a CTD probe was deployed to perform vertical profiles in 23 stations distributed throughout the GP, to characterize the variations in temperature, salinity, dissolved oxygen and chlorophyll concentration. Results: A minimum in surface and bottom temperature associated with upwelling caused by the wind was found in the first period of the year. The increase in salinity was associated with the decrease in temperature, being its highest value in the first period of the year, decreasing until reaching a minimum in November. The maximum chlorophyll concentration ​​coincided with the lowest surface temperatures and the minimum oxygen values were associated ​​with the minimum bottom temperatures, both occurring during the upwelling season. The parameter distribution was similar on dry and rainy seasons in stations located inside Bahía Culebra, likely attributed to the bathymetry effect. Conclusions: Bathymetry determines a south-north asymmetry for salinity and temperature. Subsurface cooling events coincide with strong wind periods. Upwelling influences the surface and bottom hydrographic dynamic in GP and determines the seasonal variability. The negative ENSO phase of 2018 corresponded with the strongest upwelling period, possibly promoting the interaction of upwelled coastal waters and the Costa Rica Thermal Dome.